Growth performance and suitability of Pterocymbium javanicum (melembu) as a shade tree - Mohd Pamuji, Nur Hidayah (2018)
Pterocymbium javanicum is one of the native and fast growing species of Malaysia. A trial plot was established at Ladang Ragut 3, Puchong, Universiti Putra Malaysia to evaluate the growth performance and the suitability of P. javanicum as a shade tree. This study was conducted within the period of six months, and the data was collected every three months after weeding activity. The parameters such as height, diameter, crown depth and crown width were recorded. The environmental factors that have been monitored were light intensity, temperature and relative humidity, to evaluate their effect on the growth performance of the species. The T-test study showed that there were no significant mean differences (p>0.05) in the growth parameters of P. javanicum between Plot 1 and Plot 2. In addition, weeding treatment did not have any significant effect on the growth performance of P. javanicum. Based on the characteristics of the species, it is concluded that the species is not suitable as a shade tree.